Probabilitas Tingkat Kerapuhan pada Bangunan Masjid Beton Bertulang Bertingkat Rendah Akibat Beban Seismik - Hakas Prayuda; Taufiq Ilham Maulana; Desti Lailatul Mufida Fattiha; Muhammad Mundzirul Haq; Renita Husna (MEDIA KOMUNIKASI TEKNIK SIPIL, 2025)
Building collapse is one of the leading causes of casualties during an earthquake. It is necessary to assess the resistance of the building in seismic performance in order to reduce and prevent earthquake-related damage and building collapse. With this evaluation, it is possible to predict the probability of building damage in the event of an earthquake. This study evaluates the performance of mosque buildings using the fragility curve to determine the probability level of damage. As one of the nations with the largest number of mosques in the world, Indonesia faces the challenge of overcoming the possibility of earthquake damage to the mosque buildings. In addition, many mosque buildings were built based on mutual cooperation without using detailed technical calculations. Therefore, an evaluation of the mosque structure is essential. This study employs a STERA 3D numerical simulation utilizing earthquake time history data. In this study variation, five types of earthquake time history data are utilized. Additionally, the irregular shape of the building is one of the factors under investigation. By performing a pushover analysis, the output of the capacity curve for calculations using the HAZUS method is obtained, allowing for the generation of a seismic fragility curve. The evaluation results show that different variations of time history data produce different levels of probability of damage.